The impact of pulmonary bone component embolism: an autopsy study. Issue 4 (7th January 2014) - Dettmer, Matthias S; Willi, Niels; Thiesler, Thore; Ochsner, Peter; Cathomas, Gieri
Abstract : Aims: Pulmonary bone marrow embolism (BME) and pulmonary bone fragment embolism (BFE) are two types of non-thrombotic pulmonary embolism (NTPE). While BME can be found consistently in autopsies, BFE is a rarely observed event. Both these conditions have bone lesions as source of embolism and are not considered to be causative for death. Methods: A retrospective autopsy study was performed and lung whole tissue slides were reviewed for the presence of pulmonary embolism. Clinicopathological data were screened for osseous lesions considered as risk factors for BME and BFE. Results: We reviewed 985 consecutive, unselected autopsies and identified 29 cases of BME (2.9%) and 5 cases of BFE (0.5%). Both conditions were mutually exclusive. While BME showed a significant association with costal fractures, BFE was significantly associated with osteomyelitis and previously performed femur nailing. There were between 1 and 346 bone emboli in BFE with a density ranging from 0.74 to 30.5 emboli/cm 2 with mean embolic diameter of 45.8±37.6 μm. In two patients, BFE contributed significantly to fatal outcome. Conclusions: BME was associated with costal fractures, while BFE was associated with orthopaedic procedures and osteomyelitis. BFE can result in patient death. Both conditions appeared exclusively, indicating that although they originate from osseous lesions their underlying pathogenesis may likely be different.